Menggugat Tafsir Tekstual - Juliandi, Budi; Herlambang, Saifuddin (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2016)
In this paper, some methodologies were identified that have traditionally been used by the Muslims to read the Al-Qurâan. Then, it is shown how the methodology that led to mix between the Koran and secondary religious texts, as well as resulting in the marginalization of the Koran in Muslim religious discourse, whereas the Al-Qurâan itself has a unique status as the holy book of Islam. In analyzing about textuality, studied two conceptualizations of the relationship, ie, between the word of God and the times, and the conservative approach and progressive approach, the following impact on the interpretation of the Koran. Finally, we review some of the historical trend in the formation of knowledge, methods, and religious significance, to highlight the role of the state and the entire community in the process of interpretation.